Morphology of Gut-Associated and Bronchus-Associated Lymphoid Tissues of Calves in Relation to Age - Saw, Po Po (2006)
The macroscopic, light and scanning and transmission electron microscopic structure of gut-associated lymphoid tissue (GALT) of small and large intestines and bronchus-associated lymphoid tissue (BALT) were studied in the 3, 6 and 8 monthold calves. Results showed that two different types of Peyer’s patches (discrete and continuous) were present in the small intestine. Discrete Peyer’s patches (dPP) were located in the duodenum and jejunum and continuous Peyer’s patches (cPP) were located in the ileum. The number, size, shape and distribution of Peyer’s patches (PP) in small intestine varied between individuals of the same group and between age groups. There were significantly more (p<0.05) dPP found in the jejunum part compared to that of duodenum. The number of dPP increased significantly (p< 0.05) from 3 to 6 month but this number of dPP significantly (p< 0.05) declined after 6 month of age. However, the size and distance between dPP were not significantly (p> 0.05) differences between 6 and 8 month-old calves. The cPP of the ileum was found to be raised above the level of mucosa in the 6 month-old calves. Its size decreased significantly (p< 0.05) after 6 month.Under light microscope revealed the presence of elongated follicles with very small interfollicular areas (IFAs) in ileal PP (cPP) and small pear shape follicles with large IFAs were found in the duodenal and jejunal PP (dPP). Based on the morphometric analysis, the number of jejunal lymphoid follicles and size of ileal lymphoid follicles of the 6 month-old calves were significantly higher (p<0.05) than those of 3 and 8 month-old calves. The width of IFAs of PP of small intestine increased with age. The number and size of dome of PP in small intestine of 6 month-old calves were significantly higher (p<0.05) than those of 3 and 8 month-old calves. Two types of follicle-associated epithelium (FAE), FAE of villi and FAE of crypts were found in this study. The intrafollicular invaginations of dome epithelium of duodenal PP (dPP) were found in all ages. Three morphological changes in the involuted Peyer`s patches were found in the ileum of the 8 month-old calves. The changes were: 1) the dome epithelium invaded into the follicle and formed intrafollicular surface epithelium, 2) depletion of follicle with replacement by the connective tissue and formation of acellular cavity in the follicles and 3) the domes became atrophied and all villi were thickened and shrunken. M cells in FAE of dPP were randomly distributed and the morphological structures of M cells in FAE of cPP were found to be same characteristic. SEM findings revealed that the apical surface of M cells of dPP had irregular, sparse microvilli and some M cells were completely encroached up by adjacent absorptive cells. In cPP, the luminal surface of some M cells had few or lack microvilli and various sizes of vacuoles containing particles or lymphocytes on their surface.Under the transmission electron microscope, mature and immature M cells were observed to be present in FAE of dPP and cPP of all age of studied. Mature M cells of dPP were tall columnar shape cells with less electron dense cytoplasm containing mitochondria with closely packed cristae and lymphocytes include into the cytoplasmic pocket. An irregular shaped nucleus was located toward the base of the cell and vesicles were presence at the base of microvilli. Multivesicular electrondense bodies were found in the cytoplasm of mature M cell of cPP. Immature M cells containing many mitochondria in the cytoplasm were found in lower dome epithelium. There are cytoplasmic protrusions on the luminal surface of M cells with interdigitating cell membrane at the periphery. In cPP, luminal surface of immature M cells had small microvilli and vacuole, mitochondria; rounded nucleus located at the apical part of the cell. The number and width of Peyer`s patches of large intestine varied with regions and ages. But it was not found that significantly difference (p< 0.05) between different ages. Under light microscope, the number and size of the lymphoid follicles of LGC and lymphoid nodules varied with location and age. The age related increase changes in number and size of lymphoid follicles were found in the colonic PP. The width of IFAs I the rectal and colonic PP gradually increased with increasing age. The number and size of dome of rectal PP were significantly less (p<0.05) than those of other parts of the large intestine in all age groups. The biggest domes were found in the 6 month-old calves. Under the scanning electron microscope, the star-like structures of intestinal mucosa correspond with the lamina propria nodule and the LGCs related to the pit openings of intestinal mucosa.